(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic promoted the commitment of the health system in many countries. This study retrospective was realized to evaluate the effect promoted for the pandemic in Oral and Maxillofacial Surgery and Traumatology Service at Hospital Universitario do Oeste do Paraná, in Cascavel. A sample with patients in the pandemic period, between March 16th, 2020, and March 15th, 2021, as compared with patients in the previous year, called pre-pandemic. The data was categorized by the total of patients, admission date and hourly, and etiology. Age variations and gender were evaluated also. Statistics were admitted with significance at p <0.05. The results show that there was a reduction in cases during the pandemic (n=321) compared to the pre-pandemic period (n=423 p=0.03). There was also a decrease in nighttime admissions between periods (n=126 and n=181, respectively) with significance (p=0.037). Regarding gender, the profile of male patients showed a reduction (n=220 and n=303, p=0.005). The etiology of cases of physical aggression showed a significant reduction (n=38 and n=64, p=0.016) as well as the cases of multifactorial (n = 49 and n=97, p=0.011). The period in pandemic shows association with the reduction of the patients with oral-maxillofacial trauma. The reduction of the cases in nighttime admitted as the male patient was being shown who resulted from the restriction of circulation that the pandemic imposed. The effect of consequent social distance showed a decrease in maxillofacial trauma due to physical aggression.